Spontaneous Rupture of a Leiomyoma Causing Life-Threatening Intra-Abdominal Hemorrhage - Melissa Schwartz; Kristin Powell (Hindawi Limited, 2017)
Background. Uterine fibroids are common benign tumors in women. Clinical manifestations are well known. Acute complications necessitating emergent surgical intervention are rare. Case. We report a case of a 53-year-old woman with a history of uterine fibroids presenting with acute-onset severe abdominal pain. Imaging indicated massive free fluid and a large partially solid uterine mass. Vitals were consistent with hypovolemic shock. Examination revealed a surgical abdomen. She underwent an emergent laparotomy and total hysterectomy. Surgery revealed 4.5 L of hemoperitoneum and a 15 cm degenerated uterine fibroid with active bleeding. Pathology was consistent with intraoperative findings. She required transfusion of numerous blood products perioperatively. Her postoperative course was uncomplicated. Conclusion. It is rare for a uterine fibroid to spontaneously rupture. However, prompt recognition of this severe complication is critical for expeditious, life-saving surgical management.